Evaluation of tritium production capability of the 5 MWe gas-cooled graphite-moderated reactor at Yongbyon using tritium-producing burnable absorber rods - Dokyun Kim; Seong Jeong Jeong; Hyung Jin Shim (Nuclear Engineering and Technology)
The 5 MWe graphite-moderated gas-cooled reactor located at Yongbyon, North Korea, is a major facility for producing nuclear materials. The objective of this study is to evaluate the tritium production capability of the 5 MWe reactor when using a tritium-producing burnable absorber rod (TPBAR). This paper presents burnup analysis results for TPBAR-embedded core models performed by McCARD, a Monte Carlo neutron transport simulation code. For three types of cores with TPBARs, the numerical results show that the 5 MWe reactor can produce 1.83–7.51 g of tritium per year depending on the number of TPBARs in the core. The numerical results can serve as a basis for assessing the feasibility of producing tritium using graphite-moderated gas-cooled reactors.